A participação da família na escola: um exercício de cidadania - Vanessa Leandra Dornellas Guelber (2006)
The aim of the present work is to analyze the circumstances of family participation at schools. From the final decade of last century on, the participation and engagements of parents became a legal demand in school decision processes; thus, making school committee guidance an indispensable reality in school contexts. Based upon this fact, it came to be important to verify how the referred participation takes place in an actual practice. The work began with the selection of two schools from the Belo Horizonte Municipal Education Net, where family participation does happen in a systematized way. Besides, the two schools were chosen among those which work only with the two first formation cycles and were localized in differentiated socialeconomical contexts. Predominant qualitative analysis strategies were employed and bibliographical researches taken as reference. There was no intention to make any generalizations, having in mind that this study is not sufficiently capable of reflecting the thorough reality of all the municipal schools at Belo Horizonte. Based on the hypothesis formulated in this paper, we come to the conclusion that concerning the two schools studied, the participation of parents is more effective at the school which serves people of a superior socio-economical class, than people of inferior socioeconomical standards, in spite of, in the two cases, the two schools were very receptive to this participation.